2007
DOI: 10.1007/bf03349244
|View full text |Cite
|
Sign up to set email alerts
|

A case of thyrotropin-producing pituitary adenoma, accompanied by an increase in anti-thyrotropin receptor antibody after tumor resection

Abstract: We describe a rare, but interesting, case of TSH-producing adenoma (TSHoma), accompanied by increases in both anti-TSH receptor antibody (TRAb) and thyroid-stimulating antibody (TSAb) after tumor resection. A 21-yr-old woman was referred to our department for further evaluation of pituitary tumor. In a nearby hospital, she had been diagnosed as having pituitary tumor. Her serum free T4, free T3, and TSH levels were all elevated concomitantly. On the basis of a diagnosis of pituitary adenoma with TSH production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…Therefore, a rapid reduction in the TSH levels after trans-sphenoidal tumor resection, pituitary irradiation, or octreotide administration may induce apoptosis and activate autoimmune responses against the thyroid gland as a result of increased expression of various cell surface markers (Fas, intercellular adhesion molecule-1, MHC class II) on thyrocytes [8]. In line with these hypotheses, Kageyama et al [19] reported the case of a 21-year-old woman with TSHoma who had increases in both anti-TSH receptors antibody and thyroid-stimulating antibody after tumor resection.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, a rapid reduction in the TSH levels after trans-sphenoidal tumor resection, pituitary irradiation, or octreotide administration may induce apoptosis and activate autoimmune responses against the thyroid gland as a result of increased expression of various cell surface markers (Fas, intercellular adhesion molecule-1, MHC class II) on thyrocytes [8]. In line with these hypotheses, Kageyama et al [19] reported the case of a 21-year-old woman with TSHoma who had increases in both anti-TSH receptors antibody and thyroid-stimulating antibody after tumor resection.…”
Section: Discussionmentioning
confidence: 65%
“…Fas antigen is functionally expressed on the surface of thyrocytes, and TSH inhibits Fas antigen-mediated apoptosis of thyrocytes resulting in the promotion of growth of the thyroid gland [15]. Intercellular adhesion molecule-1 and class II MHC have been implicated as contributing factors for numerous diseases, including autoimmune thyroid diseases, and TSH could downregulate their interferon-γ-mediated expression [16,17,18,19]. Therefore, a rapid reduction in the TSH levels after trans-sphenoidal tumor resection, pituitary irradiation, or octreotide administration may induce apoptosis and activate autoimmune responses against the thyroid gland as a result of increased expression of various cell surface markers (Fas, intercellular adhesion molecule-1, MHC class II) on thyrocytes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroiditis in our patient developed post therapy when the TSH levels declined from above 10 mIU/L to 1.8 mIU/L post therapy. Previously, anecdotal cases of development of Graves' disease after surgery of pituitary tumor have been described (when TSH levels declined) (7,8,16,17). The immunomodulatory role of TSH was implicated for the development of Graves' disease post surgery in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of circulating antithyroid autoantibodies is similar to that found in the general population. However, there are anecdotal case reports of patients developing Graves' disease after pituitary surgery (7,8). The immunomodulatory role of TSH with the decline in TSH levels post surgery has been implicated for autoimmune thyroid disease.…”
Section: Introductionmentioning
confidence: 99%
“…While serum TSH concentration was decreased to a normal range in response to treatment with the somatostatin analog, octreotide, the concentrations of free T3 and free T4 were not normalized and tachycardia continued. Some cases of TSHoma complicated by Graves' disease have been reported [10][11][12]. TSH is known to repress the expression of interferon-γ-induced Fas antigen [13], intercellular adhesion molecule (ICAM)-1 [14] and class II trans-activator, which is a non-DNAbinding regulator of major histocompatibility complex (MHC) transcription on the thyroid cell surface [11].…”
Section: A B Cmentioning
confidence: 99%